Effects of metal-bearing nanoparticles (Ag, Au, CdS, ZnO, SiO2) on developing zebrafish embryos. (1st July 2016) - Lacave, José María; Retuerto, Ander; Vicario-Parés, Unai; Gilliland, Douglas; Oron, Miriam; Cajaraville, Miren P; Orbea, Amaia
Abstract: Due to the increasing commercialization of consumer and industrial products containing nanoparticles (NPs), an increase in the introduction of these materials into the environment is expected. NP toxicity to aquatic organisms depends on multiple biotic and abiotic factors, resulting in an unlimited number of combinations impossible to test in practice. The zebrafish embryo model offers a useful screening tool to test and rank the toxicity of nanomaterials according to those diverse factors. This work aims to study the acute and sublethal toxicity of a set of metal-bearing NPs displaying different properties, in comparison to that of the ionic and bulk forms of the metals, in order to establish a toxicity ranking. Soluble NPs (Ag, CdS and ZnO) showed the highest acute and sublethal toxicity, with LC50 values as low as 0.529 mg Ag l −1 for Ag NPs of 20 nm, and a significant increase in the malformation prevalence in embryos exposed to 0.1 mg Cd l −1 of CdS NPs of ∼4 nm. For insoluble NPs, like SiO2 NPs, acute effects were not observed during early embryo development due to the protective effect of the chorion. But effects on larvae could be expected, since deposition of fluorescent SiO2 NPs over the gill lamella and excretion through the intestine were observed after hatching. In other cases, such as for gold NPs, the toxicity could be attributed to the presence of additives (sodium citrate) in the NP suspension, as they displayed a similar toxicity when tested separately. Overall, the results indicated that toxicity to zebrafish embryos depends primarily on the chemical composition and, thus, the solubility of the NPs. Other characteristics, such as size, played a secondary role. This was supported by the observation that ionic forms of the metals were always more toxic than the nano forms, and bulk forms were the least toxic to the developing zebrafish embryos.